Efektivitas Kinerja Pemerintah Desa dalam Pengelolaan PAMSIMAS - Nur Ummi Hani; Muin Fahmal; Nurul Qamar; Muhammad Ya'rif Arifin (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract: This study aims to determine and understand the effectiveness of the performanceof the Village Government in the Management of Community-Based Water Supplyand Sanitation Programs in Tanah Bumbu Regency. This study uses empiricalresearch methods using primary and secondary data types. The results of thisstudy indicate that the Village Government has not been effective in managing theCommunity-Based Water Supply and Sanitation Program or PAMSIMAS. This isjudged by the fact that there are still programs that do not function in severalvillages, one of which is due to facilities that can no longer be used. The generalfactors that usually become obstacles include lack of funds for asset maintenance,inadequate facilities and infrastructure, the arrival of the dry season causingwater sources to dry up, the amount of water produced is not proportional to theamount of water needed, and the condition of the soilwich are less able towithstand water infiltration. Research recommendations from the VillageGovernment should encourage the community to be active together in programutilization and asset maintenance by seeking funds either through communitycontributions or requesting assistance from the city/district government in theform of donations, or nearby companiesvillage. Country drop provide a legalumbrella made by the Regency Government so that the distribution of the budgetfor the program can run as it should and does not conflict with the applicablelaws and regulation, a well as clarify the implementing rules for maintenamce ofthe program the facility. Abstrak: Penelitian ini bertujuan untuk mengetahui dan memahami efektivitas kinerjaPemerintah Desa dalam pengelolaan Program Penyediaan Air Minum danSanitasi Berbasis Masyarakat DI Kabupaten Tanah Bumbu. Penelitian inimenggunakan metode penelitian empiris dengan menggunakan jenis data primerdan sekunder. Hasil penelitian ini menunjukkan bahwa Pemerintah Desa belumefektif dalam pengelolaan Program Penyediaan Air Minum dan Sanitasi BerbasisMasyarakat atau PAMSIMAS. Hal ini dinilai dari masih adanya program yangtidak berfungsi di beberapa desa salah satunya akibat fasilitas yang tidak dapatlagi digunakan. Adapun faktor umum yang biasa menjadi hambatan antara lain,kurangnya dana untuk pemeliharaan aset, sarana dan prasarana kurang memadai, datangnya musim kemarau menyebabkan sumber air menjadi kering,jumlah air yang dihasilkan tidak sebanding dengan jumlah air yang dibutuhkan,serta keadaan tanah yang kurang mampu menahan resapan air. Rekomendasipenelitian Pemerintah Desa seharusnya mendorong masyarakat untuk bersama-sama aktif dalam pemanfaatan program dan pemeliharan aset dengan mencaridana baik melalui iuran di masyarakat atau meminta bantuan kepadapemerintah kota/kabupaten berupa sumbangan, atau perusahaan di sekitardesa. Memberikan payung hukum yang dibuat oleh Pemerintah Kabupaten agarpenyaluran anggaran untuk program tersebut bisa berjalan sebagaimanamestinya dan tidak bertentangan dengan peraturan perundang-undangan yangberlaku, serta memperjelas aturan pelaksana untuk dilakukan pemeliharaanterhadapat fasilitas tersebut.